Spread and control of the giant African snail in the Pacific - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
The spread of the giant African snail (Achatina fulica) across the Pacific islands is still causing concern because it feeds on, anddestroys, a wide range of crops and ornamental plants. Already present in 11 Pacific countries and territories, the...